Pembajakan Hak Cipta Vidio Pada Situs Youtube Ditinjau Dalam Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Rinka, Cindyra; Irianto, Kartika Dewi (Innovative: Journal Of Social Science Research, 2024)
Intellectual Property Rights (IPR) is a type of creativity resulting from a human idea in fulfilling the needs of human life, where the case of reposting a photo or video can impact economic and moral deficits for the owner of the photo or video, in Law Number 28 of the Year 2014 concerning Copyright, if someone is irresponsible in reposting it without stating the source of the reposted photo/video. This makes the YouTube application sensitive to violations of a work containing copyrighted material which causes harm to the creator, where the owner actually gets the rights to the content which is realized in a tangible form that belongs to him. This research is research in the field of law in a normative form, where normative legal research is research that is useful for studying and researching law as rules, norms, legal doctrine, legal principles, other legal theories in order to answer the legal constraints being studied, related to copyright holders. videos that are reposted for commercial purposes.